2001
DOI: 10.1016/s0006-3495(01)76259-5
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of CAP18-Derived Peptides with Membranes Made from Endotoxins or Phospholipids

Abstract: Antimicrobial peptides with alpha-helical structures and positive net charges are in the focus of interest with regard to the development of new antibiotic agents, in particular against Gram-negative bacteria. Interaction between seven polycationic alpha-helical CAP18-derived peptides and different types of artificial membranes composed of phosphatidylcholine or lipopolysaccharide of the Gram-negative bacterium Escherichia coli were investigated using different biophysical techniques. Results obtained from flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 42 publications
7
60
2
Order By: Relevance
“…This activity occurs stepwise, beginning with attachment to the outer membrane, which induces a conformational change in the peptide resulting in insertion into the membrane (37,(57)(58)(59). In our study we found that gelsolin had no effect on either the growth of Gram-positive and Gram-negative bacterial strains or on the antibacterial activity of cathelicidin-derived LL37.…”
Section: Discussioncontrasting
confidence: 45%
“…This activity occurs stepwise, beginning with attachment to the outer membrane, which induces a conformational change in the peptide resulting in insertion into the membrane (37,(57)(58)(59). In our study we found that gelsolin had no effect on either the growth of Gram-positive and Gram-negative bacterial strains or on the antibacterial activity of cathelicidin-derived LL37.…”
Section: Discussioncontrasting
confidence: 45%
“…It is well established that LPS shields the bacteria and provides an effective barrier against hydrophilic and hydrophobic compounds (14,36). Thus, differences in activity against Gram-negative bacteria are likely to result from the interactions of peptides with LPS (37,38). Further studies are necessary to clarify this point.…”
Section: Discussionmentioning
confidence: 99%
“…The AMPs tested in this study were derivatives of the human cathelicidin LL37 (LL20 and LL32) (41), derivatives of porcine NK-lysin (NK2 and C7S) (8), and a synthetic antilipopolysaccharide (anti-LPS) peptide, Lpep 19-2.5 (5). (All were purified from chemical peptide synthesis and kindly provided by O. Holst, Division of Structural Biochemistry, and J. Andrä, Division of Biophysics, Research Center Borstel, Borstel, Germany.)…”
Section: Methodsmentioning
confidence: 99%